Mucocele of the Appendix: A Presentation - Singh, Mahendra Pratap; Huda, Tanweerul (The Surgery Journal, 2022)
The mucocele of the appendix can be described as an obstructive dilatation of the appendix by an intraluminal accumulation of mucus. A 60-year-old diabetic male patient presented with chief complains of pain in right lower abdomen for the past 2 months which was dull in nature, not associated with fever, vomiting, diarrhea, constipation, or any urinary complains. Contrast-enhanced computed tomography (CECT) of the abdomen revealed appendiceal lumen distended, filled with fluid collection. There was abrupt narrowing seen at its junction with cecum. Features were suggestive of appendicular mucocele. The patient was taken up for exploratory laparotomy, and a distended turgid appendix, around 4 cm in diameter with dilated cecum, was found. Ileocecal resection was done followed by ileo-ascending colon side-to-side anastomosis using staplers. The histopathological examination report revealed an R0 resection. The patient was followed up for 3 years postoperatively with CECT of the abdomen and a colonoscopy yearly. There was no evidence of any recurrence in the follow-up.
Keywords: mucocele; appendix; epithelial tumors